Personality Traits and Social Support: Their Role in Postpartum Depression - Richa S; Parveen S; Abullais SS; Mahmood SE; Alsamghan A; Alshaikh AA (Psychology Research and Behavior Management)
Saumya Richa,1,* Sumaila Parveen,2,* Shahabe Saquib Abullais,3,* Syed Esam Mahmood,4,* Awad Alsamghan,4,* Ayoub Ali Alshaikh4,* 1Department of Psychology, Lovely Professional University, Phagwara, Punjab, India; 2Department of Anesthesia and Operations, College of Applied Medical Sciences, King Khalid University, Muhayil Asir, Saudi Arabia; 3Department of Periodontics and Community Dental Science, College of Dentistry, King Khalid University, Abha, Saudi Arabia; 4Department of Family & Community Medicine, College of Medicine, King Khalid University, Abha, Saudi Arabia*These authors contributed equally to this workCorrespondence: Syed Esam Mahmood, Department of Family and Community Medicine, College of Medicine, King Khalid University, Al-Qaraa Campus, P.O. Box 641, Abha, 62529, Saudi Arabia, Email smahmood@kku.edu.saIntroduction: Postpartum depression (PPD) is a significant mood disorder occurring within the first year after childbirth, characterized by persistent sadness, fatigue, and bonding difficulties. This study focuses on mothers in Aurangabad, Bihar—a region with limited health-care facilities, high poverty, low education, and strong cultural beliefs about motherhood and mental health. We hypothesized that positive Big Five personality traits correlate with lower PPD levels, and that social support enhances this protective effect.Methods: This cross-sectional survey involved 300 mothers of children aged 1– 2 years, recruited via convenience sampling between February and April 2023. Data collection used face-to-face interviews with the Big Five Inventory (BFI), Multidimensional Scale of Perceived Social Support (MSPSS), and Edinburgh Postnatal Depression Scale (EPDS). Analyses included descriptive statistics, correlation analysis, moderation testing with PROCESS macro (SPSS v4.2), and Structural Equation Modeling (SEM).Results: The average EPDS score was 7.9 (SD = 4.3), indicating generally low to moderate levels of PPD. Higher depression scores were significantly associated with neuroticism (r = 0.51, p < 0.01), lower extraversion, older mothers’ age, and lower income. Perceived social support did not directly predict PPD but marginally moderated the relationship between personality traits and depression (interaction p = 0.0995), with reduced effect at higher levels of support (p = 0.2245). SEM supported partial indirect effects but did not indicate strong mediation.Conclusion: Personality traits, particularly neuroticism, are key predictors of PPD in this population. While social support shows a limited moderating effect, it may offer modest protective benefits under certain conditions. The findings underscore the need for early psychological screening, especially for neuroticism, and tailored support interventions for new mothers. Given the cross-sectional design and sampling method, results should be interpreted cautiously. Longitudinal studies are recommended for further validation.Keywords: postpartum depression, personality traits, social support, Big Five Inventory, cross-sectional study, perceived social support, moderation analysis, structural equation modeling